Children's Mental Health Visits to the Emergency Department: Factors Affecting Wait Times and Length of Stay. (19th January 2014) - Newton, Amanda S.; Rathee, Sachin; Grewal, Simran; Dow, Nadia; Rosychuk, Rhonda J.
Abstract : Objective . This study explores the association of patient and emergency department (ED) mental health visit characteristics with wait time and length of stay (LOS). Methods . We examined data from 580 ED mental health visits made to two urban EDs by children aged ≤18 years from April 1, 2004, to March 31, 2006. Logistic regressions identified characteristics associated with wait time and LOS using hazard ratios (HR) with 95% confidence intervals (CIs). Results . Sex (male: H R = 1.48, 95% C I = 1.20 –1.84), ED type (pediatric ED: H R = 5.91, 95% C I = 4.16 –8.39), and triage level (Canadian Triage and Acuity Scale (CTAS) 2: H R = 3.62, 95% C I = 2.24 –5.85) were statistically significant predictors of wait time. ED type (pediatric ED: H R = 1.71, 95% C I = 1.18 –2.46), triage level (CTAS 5: H R = 2.00, 95% C I = 1.15 –3.48), number of consultations (H R = 0.46, 95% C I = 0.31 –0.69), and number of laboratory investigations (H R = 0.75, 95% C I = 0.66 –0.85) predicted LOS. Conclusions . Based on our results, quality improvement initiatives to reduce ED waits and LOS for pediatric mental health visits may consider monitoring triage processes and the availability, access, and/or time to receipt of specialty consultations.